The first 7 - Pohl, Laura (Sourcebooks Fire, 2020)
After leaving Earth, now devastated by an alien attack, and exploring the galaxy, Clover Martinez and her fellow teen survivors return home to find crystal formations in the soil that are threatening to destroy the planet, and a colony of survivors who are not who they seem.